2013
DOI: 10.1117/12.2007308
|View full text |Cite
|
Sign up to set email alerts
|

Improved delivery of magnetic nanoparticles with chemotherapy cancer treatment

Abstract: Most nanoparticle-based cancer therapeutic strategies seek to develop an effective individual cancer cell or metastatic tumor treatment. Critical to the success of these therapies is to direct as much of the agent as possible to the targeted tissue while avoiding unacceptable normal tissue complications. In this light, three different cisplatinum/magnetic nanoparticle (mNP) administration regimens were investigated. The most important finding suggests that clinically relevant doses of cisplatinum result in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Thus, the above conditions for the AMF, duration of MHT, and injection dose of Resovist ® appear to have been appropriate for the purpose of this study. Petryk et al reported that intraperitoneal administration of CDDP at a dose of 5 mg/kg body weight improved the delivery of MNPs to tumors in C3H mice inoculated intradermally with MTG-B cells 5) and it helped to enhance the therapeutic effect of MHT 3) . Thus, we also injected CDDP into mice intraperitoneally at a single dose of 5 mg/kg body weight according to their protocol.…”
Section: Therapeutic Effectmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the above conditions for the AMF, duration of MHT, and injection dose of Resovist ® appear to have been appropriate for the purpose of this study. Petryk et al reported that intraperitoneal administration of CDDP at a dose of 5 mg/kg body weight improved the delivery of MNPs to tumors in C3H mice inoculated intradermally with MTG-B cells 5) and it helped to enhance the therapeutic effect of MHT 3) . Thus, we also injected CDDP into mice intraperitoneally at a single dose of 5 mg/kg body weight according to their protocol.…”
Section: Therapeutic Effectmentioning
confidence: 99%
“…This feature of tumor tissues is called the "enhanced permeability and retention (EPR) effect" 18) . In order to develop the EPR effect, it is important to alter the tumor vascular barrier, to increase local blood flow, and to reduce tumor interstitial fluid pressure 5) .…”
Section: Therapeutic Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…Cisplatinum pre-treatment has been shown to increase iron oxide nanoparticle deposition intratumorally in a mouse model. 6 Further studies include dose modulation, timing and chemotherapy selection in order to understand how mNP delivery can be effectively integrated with conventional chemotherapy.…”
Section: ) Tumor Modification and Vascular For Nanoparticle Uptake Imentioning
confidence: 99%